Central and peripheral pulmonary sclerosing pneumocytomas: multi-phase CT study and comparison with Ki-67 - Zhang Yanli; Ran Chao; Li Wei (Radiology and Oncology, 2023)
This study aimed to evaluate the multi-phase CT findings of central and peripheral pulmonary sclerosing pneumocytomas (PSPs) and compared them with Ki-67 to reveal their neoplastic nature.